Effects of green tea (Camellia sinensis) mouthwash containing 1% tannin on dental plaque and chronic gingivitis: a double‐blinded, randomized, controlled trial. Issue 1 (14th August 2015) - Radafshar, Golpar; Ghotbizadeh, Mahshid; Saadat, Farshid; Mirfarhadi, Nastaran
Abstract: Aim: The aim of the present study was to explore the effects of Iranian green tea mouthwash containing 1% tannin on dental plaque and chronic gingivitis. Methods: In this randomized, double‐blinded, parallel, controlled clinical trial, 40 volunteer dental students with a gingival index ≥1 were enrolled. At baseline, gingival, plaque, and bleeding indices were recorded and all the participants received dental polishing. Based on random allocation, 20 participants used the test and 20 used chlorhexidine mouthwash with no change in regular toothbrushing methods. The participants were asked to use 15 mL of the respective mouthwash for 1 min, twice a day for 28 days. All indices, as well as stain index, were recorded after 1 and 4 weeks post‐rinsing. Data were analyzed using repeated‐measures ANOVA and Bonferroni tests. Results: Significant in‐group differences, but not between‐group differences, were observed in all indices after 1 and 4 weeks compared to baseline. The test mouthwash resulted in significantly less tooth staining than the control. Conclusion: The 1% tannin green tea mouthwash could be a safe and feasible adjunct to mechanical plaque control. The tested green tea mouthwash could be considered a good alternative for chlorhexidine in contraindicating situations.